Intensification options of small holders' cassava production in south-west Nigeria - Kreye, C.; Hauser, S.; Pypers, Pieter; Vanlauwe, Bernard (Wiley, 2020)
Cassava (Manihot esculenta Crantz) is a staple food crop in Nigeria, but root yields hardly exceed 10 t ha−1. Intensification of small holders’ cassava production is key to improved food security and income generation. We tested, in two demonstration trials and 20 on‐farm trials, different intensification options: cassava growth type (erect and branching), fertilizer application (with and without), and cassava − legume arrangement (0.5 by 2 m/1 by 1 m spacing of cassava) in demonstration trials. In on‐farm trials, farmers tested a subset of these treatments. The demonstration trials had median cassava yields of about 20 (Akindele village) and 15 (Osunwoyin village) t ha−1. Fertilizer application increased the yield of the erect cassava variety. Cassava intercropped with cowpea [Vigna unguiculata (L.) Walp.], reduced yield and the branching cassava variety produced lower yield than the erect variety. Median cowpea yields were about 1 and 1.5 t ha−1 pod yield. Median yields in the on‐farm trials were about 10 t ha−1. Intercropping with cowpea reduced cassava root yields (on average by 2.4 t ha−1), again, cowpea pod yields of 1−1.5 t ha−1 were attainable. In summary, this study confirmed that intensification measures need to be site and user or farmer specific.